Germany : Financial Sector Assessment Program: Detailed Assessment of Observance of IOSCO Objectives and Principles of Securities Regulations. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2011)
Germany has a comprehensive legislative and institutional framework for the effective supervision of the securities markets. The overall level of compliance with the IOSCO principles is high. There are significant industry concerns about the implementation costs resulting from a rapidly changing legislative framework. The German Federal Financial Supervisory Authority (BaFin's) overall approach to supervision relies very heavily on the flow of information, auditors' reports, and compliance with legislative obligations. Regulators at both the federal and state levels work with a clear legal framework and clearly defined powers and responsibilities.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet